Discovering the giant nest architecture of grass-cutting ants, Atta capiguara (Hymenoptera, Formicidae) - Forti, Luiz Carlos [UNESP] (2017)
Atta capiguara is a grass-cutting ant species frequently found in Cerrado biome. However, little is known about the giant nest architecture of this ant. In this study, we investigated the architecture of three A. capiguara nests from a fragment of Cerrado in Botucatu, São Paulo, Brazil. Casts were made of the nests by filling them with cement to permit better visualization of internal structures such as chambers and tunnels. After excavation, the depth and dimensions (length, width, and height) of the chambers were measured. The results showed the shape of Atta capiguara nests consisting of mounds of loose soil with unique features resembling a conic section. The fungus chambers were found distant from the mound of loose soil and were spaced apart and distributed laterally at the soil profile. The waste chambers were located beneath the largest mound of loose soil. Both the fungus and waste chambers were separated and distant. Our study contributes to a better understanding of the so far unknown nest architecture of the grass-cutting ant A. capiguara.